2007
DOI: 10.1371/journal.pone.0001142
|View full text |Cite
|
Sign up to set email alerts
|

Ets-1 Confers Cranial Features on Neural Crest Delamination

Abstract: Neural crest cells (NCC) have the particularity to invade the environment where they differentiate after separation from the neuroepithelium. This process, called delamination, is strikingly different between cranial and trunk NCCs. If signalings controlling slow trunk delamination start being deciphered, mechanisms leading to massive and rapid cranial outflow are poorly documented. Here, we show that the chick cranial NCCs delamination is the result of two events: a substantial cell mobilization and an epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 46 publications
6
116
1
Order By: Relevance
“…Similarly, ectopic expression of the Ets1 transcription factor induces NE cell delamination independently of a NC phenotype but fails to promote migration. Expressing both Snail2 and Ets1 confers full capacity to migrate (Théveneau et al, 2007), and knocking down Snail2 does not alter NC delamination but results in apoptosis during migration (Cheung et al, 2005;Teng et al, 2008). These observations indicate that NE cell ability to delaminate is not sufficient for adopting NC features and that, conversely, acquisition of NC identity is not necessary for delamination but is a prerequisite for survival.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, ectopic expression of the Ets1 transcription factor induces NE cell delamination independently of a NC phenotype but fails to promote migration. Expressing both Snail2 and Ets1 confers full capacity to migrate (Théveneau et al, 2007), and knocking down Snail2 does not alter NC delamination but results in apoptosis during migration (Cheung et al, 2005;Teng et al, 2008). These observations indicate that NE cell ability to delaminate is not sufficient for adopting NC features and that, conversely, acquisition of NC identity is not necessary for delamination but is a prerequisite for survival.…”
Section: Discussionmentioning
confidence: 92%
“…to provoke EMT of neural epithelial cells (del Barrio and Nieto, 2002;Cheung et al, 2005;Theveneau et al, 2007). All together, these observations suggest possible antagonistic roles for Snail-2 and Zeb-2 in the control of EMT in neurectodermal cells, irrespective of their function as cadherin regulators.…”
Section: Fig 2 Expression Patterns Of E-and N-cadherins and Their Tmentioning
confidence: 98%
“…In summary, cranial NC cell delamination occurs all at once and massively in a discrete portion of the neural epithelium, immediately after its invagination, all features characteristic of en masse EMT. [54][55][56] In contrast to the head, the onset of NC cell delamination in the trunk is clearly uncoupled from closure of the neural tube, indicating that, in this region, the determinism of the triggering of EMT does not reside in the fold fusion (Fig. 4B).…”
Section: The Neural Crest a Cell Population Issued By An Emtmentioning
confidence: 99%
“…In striking contrast with the massive and rapid emergence of cranial NC cells, truncal NC cells emigrate individually from the dorsal neural tube, in a dripping fashion over a long period of time extending beyond 40 h. [59][60][61][62] This very gradual segregation of NC cells in the trunk stems primarily from the fact that in this region, EMT is coupled to the cell cycle. 55,63 In the avian embryo, NC cells synchronously emigrate from the neural tube in the S-phase, when the nucleus is closest to the basal side, and specific inhibition of the G 1 /S transition provokes severe reduction in delamination, without affecting specification. 63 Moreover, recent studies have shown that NC cell progenitors are initially distributed in a broad region in the dorsal region of the neural tube and that they become gradually confined to a narrow band at the apex of the tube as delamination progresses.…”
Section: The Neural Crest a Cell Population Issued By An Emtmentioning
confidence: 99%
See 1 more Smart Citation